Assessment of the Effectiveness of a Film-Forming Cream in the Management of Oral Aphthous Ulcers: A Placebo-Controlled Randomized Clinical Trial - Simone Marconcini; Giacomo Oldoini; Annamaria Genovesi; Enrica Giammarinaro (The Korean Society of Dental Hygiene Science, 2023)
Background: Aphthous stomatitis is a common disease of the oral mucosa and its pathogenesis is associated with several risk factors. Frequently, minor ulcers are idiopathic in nature and often resolve naturally. However, those ulcers are painful and sensibly compromise patients' eating. There are different treatment strategies for the clinical management of oral aphthae. Methods: The present study assessed the efficacy of a film-forming cream in accelerating the healing and diminishing the pain associated with minor aphthae in a randomized fashion design. The test product (AphtoFixⓇ) was compared with placebo cream in a cohort of patients with a diagnosis of minor recurrent stomatitis. Patients were randomly distributed into two groups and were followed for 10 days. The primary outcomes included the number of days until symptoms were relieved and the number of days to complete healing. Results: Thirty-six patients completed the follow-up, eighteen per group. All lesions eventually healed within day 10. However, patients in the test group experienced significantly less pain, already from day 1. Patients in the test group also showed a faster healing rate of the lesion with an average of 7 days against the 9 days required for patients in the control group. Conclusion: The present study supported the utility of a film-forming in cream in relieving the patient from symptoms associated with aphthous stomatitis already at day 1 of product use. Patients also displayed faster healing of the lesions when compared to the control group. Further studies with greater sample size and patient stratification according to age and risk factors are recommended to support the present findings.